Anredera cordifolia (Ten.) Steenis [Basellaceae]: A New Record for Eastern India from Darjeeling District of West Bengal - Katuwal, Panchami; Chhetri, Siddhu; Naskar, Chandan; Prasad, Ravi; Biswas, Kishor (Indian Forester, 2024)
No Abstract.